A gender-sensitive analysis of the feasibility and benefit of a psychological intervention for patients with advanced cancer. Issue 3 (13th July 2022) - Shapiro, Gilla K.; Mah, Kenneth; de Vries, Froukje E.; Zimmermann, Camilla; Li, Madeline; Hales, Sarah; Rodin, Gary
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: The role of gender in psychotherapy has been widely recognized but infrequently investigated in psychotherapy trials. We conducted a secondary analysis of data from a randomized controlled trial of Managing Cancer and Living Meaningfully (CALM), a supportive-expressive intervention for individuals with advanced cancer, to examine gender effects in the feasibility, acceptability, perceived benefit, and effectiveness of CALM. Methods: Trial participants, outpatients with advanced cancer (N = 305, 40% men and 60% women), completed measures at baseline, 3 months ( t 1), and 6 months ( t 2). We investigated gender differences in participation rates, attrition rates, number of CALM sessions received, and perceived benefit of CALM. Separate subgroup analyses of data and gender × treatment group moderator analyses from men and women were compared in examining treatment effects on depressive symptoms, end-of-life preparation, and death anxiety at each follow-up period. Results: No gender differences were observed in participation or attrition rates, number of CALM sessions received, or perceived benefit of CALM. In subgroup analyses at t 2, men in CALM reported significantly lower depressive symptoms than men in usual care (UC; P = .017), women in CALM with moderate baseline death anxiety reported lower death anxiety than women in UC ( P = .009), and both men ( P = .022) and women ( P = .016) in CALM reported greater end-of-life preparation than those in UC. There were no significant gender × treatment group interaction effects on any outcome. Conclusions: CALM therapy is feasible, acceptable, and beneficial on different outcomes for men and women. Further clinical trials with comprehensive measures of gender identity are needed to evaluate gender effects in psychotherapeutic interventions for patients with advanced disease.